Da guerra à paz? Dicotomias que escondem múltiplos caminhos: análise histórica sobre os "Cayapó" aldeados em Maria I e São José de Mossâmedes - Asnis, Gabriel Zissi Peres (2019)
The dissertation aims to analyze part of a historical and ethnographic documentation about the former captaincies of São Paulo and Goiás, with a view to the study of historical processes of contact between indigenous populations and colonial fronts in the 18th and 19th centuries. Based on the dialogue between Anthropology and History, the main challenge is to understand how the symbolic structures order the history, as well as the history orders the symbolic structures. From a concrete context: the history of the contacts of groups of the Meridional Jê, documentally known as "Cayapó", with its different others, the intention is to contribute to the re-evaluation of a history of these groups. Marked by moments of war and "pacification", what we want to show is how this story was not linear or successive but discontinuous, mutant and changing, resulting from the confrontation between symbolic structures and pragmatic interests. For a long time, the histories of these Jê groups have neutralized them as active participants in their own history. The documentary sources and part of the historiography considered only the vision of the non-indigenous and therefore did not stop in the study of the cultural structures and the interests of the indigenous groups in the evaluation of their historical action. For this reason, the history of the contacts was marked by the discourses, for the most part, prejudiced and subjective. In view of this, the main objective was to analyze the documentation that mentions the indigenous populations that inhabited the studied region in order to reveal the alterity present in the documentation. Developed on the basis of the index paradigm, the basic research material consisted of both historical documentation of the XVIII and XIX centuries referring to the mentioned region; as an ethnographic and historical bibliography on the Kayapó, that allowed the exercise of an ethnographic projection.